Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Guru SD Al-Muttaqin di Kota Tasikmalaya - Lintan Nurhalisah,; Kusuma Agdhi Rahwana,; Arga Sutrisna, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the effect of compensation and work environment on performance (a survey of elementary school teachers at Al- Mutaqqin Foundation, Tasikmalaya City). The method used in this study is causality through a census approach. With a research sample of 68 elementary school teachers, Al-Mutaqqin Foundation, Tasikmalaya City. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that compensation has a very good assessment classification, the work environment has a very good assessment classification, while employee performance has a good classification for elementary school teachers at Al-Mutaqqin Foundation, Tasikmalaya City. Taken together, compensation and work environment have a significant effect on employee performance at the Al-Mutaqqin Foundation Elementary School Teacher, Tasikmalaya City. Partially, compensation has a significant effect on employee performance at the Al-Mutaqqin Foundation Elementary School Teacher, Tasikmalaya City. Partially, the work environment has a significant effect on employee performance at the Al-Mutaqqin Foundation Elementary School Teacher, Tasikmalaya City